Developing a hybrid solar/fuel cell converter for electric vehicles - Mohamed Saumee Mohamed Sulhan. (2010)
Solar cells and fuel cells form a good alternative energy sources for isolated load. A hybrid solar/fuel cell DC-DC converter can be very attractive nowadays. The project started from literature research of solar cells and fuel cells, maximum power point tracker (MPPT), DC-DC converter and DC machine. The project aims to construct and simulate solar cell and fuel cell sources, MPPT circuits, DC-DC converter and DC machine. Also, the project aims to develop the hardware of the hybrid solar/fuel cell converter. The various electrical circuits are simulated using PSIM software. This project deals with the simulation of solar cell and fuel cell sources which are enhanced by a Maximum Power Point Tracker (MPPT) circuit which will track and extract the maximum power from the solar and fuel cell sources. Finally, a DC-DC converter is designed and implemented for power conditioning, to get the required/suitable voltage to drive the DC motor load. Therefore the goal of this project is to perform a systematic research, modeling and developing the key subsystems or components of a hybrid solar and fuel cell converter with optimal tracking and control strategy.